The copper-bismuth-sulphur material system and thin film deposition of Cu3BiS3 by sputtering and evaporation for the application of photovoltaic cells - McCracken, Robert O. (Cranfield University, 2016)
The semiconducting sulphosalt Wittichenite has been identified as a possible absorber material for thin film photovoltaic devices. It has the chemical formula Cu3BiS3 and its component elements are those of low toxicity and high abundance making it a very attractive prospect for photovoltaic devices. The copper bismuth sulphur material system is not very well understood and information on it limited to a few small regions. To aid understanding of this system a pseudo-binary phase diagram along the CuS-Bi join of the Cu-Bi-S ternary phase diagram was constructed by making bulk samples of various compositions along the join and analysing them using X-ray diffraction and differential scanning calorimetry. This join was chosen because is crosses the point at which Cu3BiS3 would be expected to occur due to its stoichiometry. The CuS-Bi phase diagram shows Cu3BiS3 forms across a wide compositional range but is mixed with either bismuth metal or copper sulphides depending on composition. Films of Cu3BiS3 were made using sputtered copper and bismuth films annealed in a sulphur atmosphere and thermal co- evaporation of copper sulphide and bismuth.
Keywords: Photovoltaic cells; Solar cells; Thin films